PENINGKATAN MOTIVASI BELAJAR SISWA MEMBUAT SULAMAN PIPIH MELALUI STRATEGI CTDL DI SMPN 4 PAYAKUMBUH - Is, Warnita; Zahri, Wildati; Idrus, Yenni (Journal of Home Economics and Tourism, 2012)
This study aims to improve students' motivation to make embroidered tablecloth flat for ornament through direct type of cooperative learning strategies in SMP N 4 Payakumbuh. Motivation student views of the three indicators, namely pleasure seeking and problem solving, passionate and hard-working, persevering in the face of duty. This type of research is a classroom action research consists of the first cycle and second cycle of each cycle of three meetings, one meeting two times 40 minutes. Data collection techniques were observation technique of quantitative and qualitative data analysis. The results showed that students' motivation on the indicators have been achieved, with the achievement of the targets set is 80%. Thus, Type Direct Cooperative Learning Strategies in the learning process can improve students' motivation, to make flat embroidery to decorate the table.